Metals in water, sediments and fish collected in São Vicente-SP estuary, Brazil - Do Carmo, Carolina Almeida; De Souza Abessa, Denis Moledo; Neto, Joaquim Gonçalves Machado [UNESP] (Centro Universitario Sao Camilo - Sao Paulo, 2011)
São Vicente estuary, located in Baixada Santista, presents increasing levels of pollution caused by urbanization and the installation of polluting sources. The objective of this work was to evaluate the distribution of some metals (iron, chromium, nickel, zinc, manganese and copper) in the different environmental compartments that compose the aquatic ecosystem of Branco and Mariana Rivers estuaries, located in São Vicente Estuary. We analyzed samples of water and branchial and hepatic sediments and tissues of white mullet (Mugil curema) in the two rivers. The determination of metals in samples was carried through in Atomic Absorption Spectrophotometer GBC®. The average concentrations of chromium, nickel and zinc in waters of both rivers were above the limits established by the Brazilian legislation for brackish waters, but metal levels were higher in samples from Mariana River. In the sediments, the highest concentrations were in samples from Rio Branco, which also exceeded international legislation guiding values: Cu, Ni and Zn exceed the thresholds of toxic effect - TEL while for Cr the level of probable effect - PEL was exceeded. In fish tissues, Fe, Cr and Ni had presented a higher accumulation in the gills, while Zn, Mn and Cu had occurred in higher concentrations in liver tissues, and this relates to mechanisms of purification relative to the different elements. In most cases, the fish of the two rivers presented similar metal levels in their tissues, but the animals from Rio Branco had higher concentrations of Fe and Cu, while those of Mariana River presented higher quantities of Mn in the gills. It was not possible to establish relationships between environmental contamination and metals in fish tissues, but values found in samples of water, sediments and tissues are higher the ones described in the literature and show a worrying situation that requires the identification and control of polluting sources.
Metais em águas, sedimentos e peixes coletados no estuário de São Vicente-SP, Brasil
Keywords: Brazil - baixada santista; Contamination of water; Metals